Accelerating vaccine trial conduct in a pandemic with a hot spot‐based inclusion strategy using trial and epidemic simulation. Issue 6 (14th July 2021) - van der Plas, Johan L.; van Esdonk, Michiel J.; Kamerling, Ingrid M. C.; Cohen, Adam F.
Abstract: Clinical development of vaccines in a pandemic situation should be rigorous but expedited to tackle the pandemic threat as fast as possible. We explored the effects of a novel vaccine trial strategy that actively identifies and enrolls subjects in local areas with high infection rates. In addition, we assessed the practical requirements needed for such a strategy. Clinical trial simulations were used to assess the effects of utilizing these so‐called "hot spot strategy" compared to a traditional vaccine field trial. We used preset parameters of a pandemic outbreak and incorporated realistic aspects of conducting a trial in a pandemic setting. Our simulations demonstrated that incorporating a hot spot strategy shortened the duration of the vaccine trial considerably, even if only one hot spot was identified during the clinical trial. The active hot spot strategy described in this paper has clear advantages compared to a "wait‐and‐see" approach that is used in traditional vaccine efficacy trials. Completion of a clinical trial can be expedited by adapting to resurgences and outbreaks that will occur in a population during a pandemic. However, this approach requires a speed of response that is unusual for a traditional phase III clinical trial. Therefore, several recommendations are made to help accomplish rapid clinical trial setup in areas identified as local outbreaks. The described model and hot spot vaccination strategy can be adjusted to disease‐specific transmission characteristics and could therefore be applied to any future pandemic threat.